Peran Kelompok Wanita Tani Bawang Merah Dalam Pemberdayaan Masayarakat Di Desa Tongko Kecamatan Baroko Kabupaten Enrekang - Hasniar; Ramsiah Tasruddin; Hamriani (Jurnal Berita Sosial, 2024)
This research has three objectives, namely to find out the role of women’s onion farming groups in empowering women, to find out the results of women’s empowerment through women’s onion farming groups, to find out what obstacles the women’s onion farming groups face in empowering women which is carried out in Tongko Village, Baroko District, Enrekang Regency. This research uses a descriptive qualitative approach method which is carried out by examining a problem and then the results will be described. The approach method that researchers use is a sociological approach. Data collection was carried out using observation, interviews and documentation techniques, to prove the validity of the data, using persistence techniques in the field and triangulation of sources and methods. Data analysis in this research uses an interactive model, namely data collection, data reduction, data presentation and drawing conclusions. The research results show that women’s shallot farming groups play an important role in empowering women and as a means of increasing income from agricultural products, especially shallots, as a means of improving education and as a place to expand knowledge, through regular meetings and coaching women’s farmer groups. With these activities, members will be able to increase their income and reduce their daily needs. The results of each shallot activity in Tongko Village, Baroko District, Enrekang Regency can be used by each member to meet their daily needs, especially the women.